The Genesis of Greek Science in " The Intellectual Adventure of Ancient Man" - Dom, Adi Setia Muhammad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Genesis of Greek Science in " The Intellectual Adventure of Ancient Man"